2016
DOI: 10.5755/j01.ms.22.1.9022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Lime Mortar Used in Historical Buildings in Becin, Turkey

Abstract: It is of great importance that the architectural and engineering disciplines work together in the restoration studies of historical buildings which are our cultural heritages. It is required that the bearing system and the materials of the structures should be investigated in detail prior to any conservation. The determination of the properties and compositions of the mortar material used in the construction of the historical building is one of the most important phases of the conservation studies and it is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…As a building fabric, these pore structures are responsible for the mortar's durability against environmental conditions as they accommodate growth of ice crystal within, in frost periods, without deteriorating the matrix [8], [9]. The permeability feature also reduces moisture entrapment within, a phenomenon known as "breathability" [8], [10]- [12]. Increased bond between mortar and substrate is facilitated through lime mortar's enhanced workability resulting from its high water retention property [5].…”
Section: Introductionmentioning
confidence: 99%
“…As a building fabric, these pore structures are responsible for the mortar's durability against environmental conditions as they accommodate growth of ice crystal within, in frost periods, without deteriorating the matrix [8], [9]. The permeability feature also reduces moisture entrapment within, a phenomenon known as "breathability" [8], [10]- [12]. Increased bond between mortar and substrate is facilitated through lime mortar's enhanced workability resulting from its high water retention property [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is a plastic material that is slow to harden but allows movements within the mortar joints, without compromising its structural stability. Lime mortar has also been shown to exhibit great permeability, which enables it to reduce moisture entrapment, a phenomenon known as "breathability" [12][13][14][15]. Greater environmental awareness of its ASTESJ ISSN: 2415-6698 advantages in terms of carbon dioxide emissions during manufacture (20% less than that of cement) and subsequent adsorption during carbonation promotes its use [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Other sources stated that the compressive strength of mortars obtained from hydraulic lime can be quite low depending on the materials used and other factors. A study investigating the ancient brickwork in Becin (Turkey, 14th century) reported the compressive strength of hydraulic lime mortar to be 1.00–3.86 MPa [9].…”
Section: Introductionmentioning
confidence: 99%